Analisis Energy Produksi Biodiesel dengan Metode Metanol Super Kritis - Argo, Bambang Dwi; Gunarko, Gunarko (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
Supercritical methanol process has several advantages, that is not influenced by the material conditions for the free fatty acids contained in the materials will be esterified into methyl esters directly, the conversion rate of oil into methyl ester of tall, shorter process time and not influenced by the presence of water. However, this method has a weakness that is the need safety treatment because the process involves high temperatures and pressures. Super critical methanol method has a 2-stage hydrolysis process which took place on the state of the sub critical water to separate the free fatty acid (FFA) and glycerol, methanolyisis place on super critical conditions of methanol with the aim of changing the FFA to biodiesel, both processes take place at a temperature of 270 Â° C and pressure of 70-20 MPa.. From the research of biodiesel production process using supercritical methanol without catalyst, the reaction time is faster total reaction time of 9250 seconds (2.57 hours), with the result of more production (400 ml biodiesel) from the raw material 5% water (35 ml ), cooking oil 95% (665 ml), and 95% wt methanol (200 ml), has a 52.39% energy efficiency.Keywords : Biodiesel, methanol super critical, energy.